Recommendations for respiratory management of patients with spinal muscular atrophia (Archives of Pediatrics of Uruguay, 2021)
Spinal Muscular Atrophy (SMA) is a disease of the anterior horn of the spinal cord, genetically determined, and caused by deficiency of survival motor neuron (SMN) protein. Muscle weakness leads to a progressive decrease in vital capacity and to diminished cough flows. Respiratory morbidity and mortality are a function of respiratory and bulbar-innervated muscle impairment. It can be measured by the sequential evaluation of vital capacity to determine the life time maximum (plateau) and its subsequent rate of decline, progressing to ventilatory failure. Bulbar-innervated muscle impairment can also be monitored and measured by spirometry. The more severe clinical forms of SMA, especially those with earlier onsets and paradoxical breathing, have lower vital capacities and cough peak flows. The sequential assessment of these parameters is key for the vital and functional prognosis of these patients. SMA sub-classification types 1 and 2 of SMA involve appropriate times for non-invasive respiratory interventions in early childhood and school age and improve afterlife and quality of life. This document summarizes these recommendations, as a function of SMA type, with special reference to interventions that include air stacking, manually and mechanically assisted coughing protocols and noninvasive ventilatory support techniques, even for patients who have no ventilator-free breathing ability to minimize or eliminate the need to resort to tracheotomy. Failure to properly evaluate these patients regularly reduces their survival and chances to avoid invasive airway tubes.
Keywords: Spinal muscular atrophy; Noninvasive ventilation; Vital capacity